Spectrophotometric Simultaneous Determination of Salbutamol Sulfate and Ketotifen Fumarate in Combined Tablet Dosage Form by First-Order Derivative Spectroscopy Method. (1st September 2013) - Joshi, Parth R.; Parmar, Shraddha J.; Patel, Bhavna A.
Abstract : Salbutamol sulfate and ketotifen fumarate are used in combination for the treatment of asthma. The present work deals with method development for simultaneous estimation of salbutamol sulfate and ketotifen fumarate in two-component tablet formulation by first-order derivative spectroscopy. For determination of sampling wavelength, 10  μ g/mL of each of salbutamol and ketotifen was scanned in 200–400 nm ranges and sampling wavelengths were found to be 257 nm for salbutamol and 278 nm for ketotifen in first-order derivative spectroscopy. In this method, linearity was observed in the ranges of 5–45  μ g/mL for salbutamol and 5–35  μ g/mL for ketotifen. The % recovery was within the range between 98 and 102%, and % relative standard deviation for precision and accuracy of the method was found to be less than 2%. The method is validated as per international conference on harmonization guidelines. The method can be successfully applied for the simultaneous analysis of both drugs in pharmaceutical dosage forms.